The Utility of Skeletal and Surgical Features for the Personal Identification Process: A Pilot Study. Issue 6 (25th June 2019) - Cappella, Annalisa; Gibelli, Daniele; Obertová, Zuzana; Cummaudo, Marco; Castoldi, Elisa; De Angelis, Danilo; Sforza, Chiarella; Cattaneo, Cristina
Abstract: This pilot study provides a conceptual framework for the application of the anthropological analysis of skeletal features and surgical interventions for the purpose of identification in cases of unknown deceased individuals with unavailable fingerprint, genetic or odontological antemortem data. The study sample includes 276 individuals with known demographic and clinical information from the Italian CAL Milano Cemetery Skeletal Collection. In the sample, 124 (45%) individuals showed one or more skeletal features that may be potentially individualizing. Of these, 79% showed two and more features, which occurred in a multitude of different combinations. Skeletal findings may provide useful postmortem information that can be compared with antemortem witness statements and clinical imaging. However, more research into the utility of dry bone findings and the availability of comparative material, including imaging, and epidemiological data needs to be undertaken before skeletal features can be implemented into identification protocols and databases.